2014
DOI: 10.4143/crt.2013.114
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Intractable Bleeding Caused by Radiation-Induced Hemorrhagic Gastritis Using Oral Prednisolone: A Case Report

Abstract: Radiation-induced hemorrhagic gastritis is an intractable and dangerous condition. We describe a 59-year-old female patient with radiation-induced hemorrhagic gastritis. The patient underwent postoperative radiation therapy with a dose of 54 Gy in 30 fractions after a radical operation for a Klatskin tumor. Radiation volume included the gastric antrum. Approximately three months after radiation therapy, she was admitted for melena and anemia. Esophagogastroduodenoscopy showed an area of bleeding in the gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…This type of autoimmune disease is common for clinical tumor treatment in which the stomach is within the field of radiotherapy. Gastritis typically appears after the gastric exposure to doses higher than 40–50 Gy [ 96 ]. Although the molecular mechanisms of gastritis following exposure to radiation have not been completely determined, several studies have reported that the suppression of inflammation using anti-inflammatory drugs can help control this condition [ 97 99 ].…”
Section: Evidence Of Ir-induced Autoimmune Diseasesmentioning
confidence: 99%
“…This type of autoimmune disease is common for clinical tumor treatment in which the stomach is within the field of radiotherapy. Gastritis typically appears after the gastric exposure to doses higher than 40–50 Gy [ 96 ]. Although the molecular mechanisms of gastritis following exposure to radiation have not been completely determined, several studies have reported that the suppression of inflammation using anti-inflammatory drugs can help control this condition [ 97 99 ].…”
Section: Evidence Of Ir-induced Autoimmune Diseasesmentioning
confidence: 99%
“…Epsilon aminocaproic acid, a fibrinolytic inhibitor which acts by inhibiting plasminogen and antiplasmin activity has also been used [ 8 ]. Initial therapy with oral prednisolone [ 9 ] and rescue therapies like bevacizumab [ 10 ] have also been tried. Shukuwa et al [ 11 ] described a case of hemorrhagic radiation gastritis after being treated for pancreatic cancer managed with APC successfully.…”
Section: Discussionmentioning
confidence: 99%
“…It manifests as an edematous change in the mucosa and multiple telangiectasias in the irradiated area, resulting in hemorrhage [9]. RT-induced hemorrhagic gastric disease has been reported in a few case reports, most of which were from gastrointestinal malignancy cases [1011121314]. Das et al [10] reported nine cases of gastric bleeding following RT for intrahepatic cholangiocarcinoma and suggested that the risk of RT-related gastric bleeding was most relevant to V 40 and V 50 of the stomach.…”
Section: Discussionmentioning
confidence: 99%